Iterative Chemical Engineering of Vancomycin Leads to Novel Vancomycin Analogs With a High in Vitro Therapeutic Index - Mishra, Nigam M.; Stolarzewicz, Izabela; Cannaerts, David; Schuermans, Joris; Lavigne, Rob; Looz, Yannick; Landuyt, Bart; Schoofs, Liliane; Schols, Dominique; Paeshuyse, Jan; Hickenbotham, Peter; Clokie, Martha; et al. (Frontiers in Microbiology, 2018)
Vancomycin is a glycopeptide antibiotic that inhibits transpeptidation during cell wall synthesis by binding to the D-Ala-D-Ala termini of lipid II. For long, it has been used as a last resort antibiotic. However, since the emergence of the first vancomycin-resistant enterococci in 1987, vancomycin resistance has become widespread, especially in hospitals. We have synthesized and evaluated 110 vancomycin analogs modified at the C-terminal carboxyl group of the heptapeptide moiety with R2NHR1NH2 substituents. Through iterative optimizations of the substituents, we identified vancomycin analogs that fully restore (or even exceed) the original inhibitory activity against vancomycin-resistant enterococci (VRE), vancomycin-intermediate (VISA) and vancomycin-resistant Staphylococcus aureus (VRSA) strains. The best analogs have improved growth inhibitory activity and in vitro therapeutic indices against a broad set of VRE and methicillin-resistant S. aureus (MRSA) isolates. They also exceed the activity of vancomycin against Clostridium difficile ribotypes. Vanc-39 and Vanc-42 have a low probability to provoke antibiotic resistance, and overcome different vancomycin resistance mechanisms (VanA, VanB, and VanC1).